Cost‐effectiveness of human papillomavirus vaccination for adolescent girls in Punjab state: Implications for India's universal immunization program. Issue 17 (4th May 2017) - Prinja, Shankar; Bahuguna, Pankaj; Faujdar, Dharmjeet Singh; Jyani, Gaurav; Srinivasan, Radhika; Ghoshal, Sushmita; Suri, Vanita; Singh, Mini P.; Kumar, Rajesh
Abstract : BACKGROUND: Introduction of human papillomavirus (HPV) vaccination for adolescent girls is being considered in the Punjab state of India. However, evidence regarding cost‐effectiveness is sought by policy makers when making this decision. The current study was undertaken to evaluate the incremental cost per quality‐adjusted life‐years (QALYs) gained with introduction of the HPV vaccine compared with a no‐vaccination scenario. METHODS: A static progression model, using a combination of decision tree and Markov models, was populated using epidemiological, cost, coverage, and effectiveness data to determine the cost‐effectiveness of HPV vaccination. Using a societal perspective, lifetime costs and consequences (in terms of QALYs) among a cohort of 11‐year‐old adolescent girls in Punjab state were modeled in 2 alternate scenarios with and without vaccination. All costs and consequences were discounted at a rate of 3%. RESULTS: Although immunizing 1 year's cohort of 11‐year‐old girls in Punjab state costs Indian National Rupees (INR) 135 million (US dollars [USD] 2.08 million and International dollars [Int] 6.25 million) on an absolute basis, its net cost after accounting for treatment savings is INR 38 million (USD 0.58 million and Int 1.76 million). Incremental cost per QALY gained for HPV vaccination was found to be INR 73 (USD 1.12 and Int 3.38). Given all the data uncertainties, there is a 90% probability for the vaccination strategy to be cost‐effective in Punjab state at a willingness‐to‐pay threshold of INR 10, 000, which is less than one‐tenth of the per capita gross domestic product. CONCLUSIONS: HPV vaccination appears to be a very cost‐effective strategy for Punjab state, and is likely to be cost‐effective for other Indian states. Cancer 2017;123:3253‐60 . © 2017 American Cancer Society . Abstract : Introduction of the human papillomavirus vaccination for adolescent girls is being considered in the Punjab state of India. However, evidence regarding its cost‐effectiveness is sought by policy makers when making this decision. The results of the current study indicate that human papillomavirus vaccination is a very cost‐effective strategy for Punjab state, and is likely to be cost‐effective for other Indian states.